Bilateral psoas abscess caused by Janibacter terrae, an unusual condition and organism resulting in laboratory and management conundrums. Issue 5 (3rd September 2017) - Wan, Wei Yee; Mughal, Ahsan; Ward, Kelly
Abstract : Psoas abscess is commonly regarded as an unusual cause for back pains and usually associated with significant risk factors or co-morbidities. We describe the clinical presentation and findings of a young male Caucasian with bilateral psoas abscesses caused by an unusual organism, Janibacter terrae (an environmental organism) not previously described in literature and the challenges faced in managing this infection. There are very few case reports of this organism causing opportunistic infections, all reported bacteraemia mainly in patients with significant co-morbidities. This case highlights the importance of psoas abscess as a differential diagnosis in patients presenting with back pain and the potential for this organism to cause abscesses in healthy individuals which was difficult to identify using conventional laboratory methods. Management of this infection was challenging and there is limited experience with antimicrobial treatment for this organism.